Gastric Microbiota in Patients with Dyspepsia: Metatranscriptomic Analysis - Е. А. Kupriyanova; М. I. Markelova; Е. А. Ziyatdinova; D. D. Safina; A. G. Safin; I. М. Alieva; R. К. Zalyalov; R. А. Abdulkhakov; Т. V. Grigoryeva; S. R. Abdulkhakov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim: to assess the composition of the microbiota of the mucous membrane of the body and the antrum of the stomach.Materials and methods. Sixty patients with dyspeptic symptoms were included into the study. Two biopsy samples of the gastric mucosa (from the body of the stomach and the antrum) were obtained from each patient. The presence of H. pylori infection was confirmed by PCR; RNA was isolated and then libraries were prepared for metatranscriptomic analysis of the 16S rRNA gene. Sequencing was performed on MiSeq (Illumina, USA) using MiSeq Reagent Kit v3 (600-cycle) (Illumina, USA).Results. The bacterial diversity decreases with the predominance of Helicobacter pylori species in H. pylori-positive patients. These results were confirmed by the Shannon index, the average value of which was 3.6 in the H. pylori-positive group and 5.4 in the H. pylori-negative group. In H. pylori-negative patients an increase in the representation of Streptococcus, Prevotella and Alloprevotella genera was observed. The level of H. pylori contamination of the gastric mucosa varies in the antrum and body of the stomach, in some cases reaching a 3.5-fold difference. Representation of other bacteria in the body and antrum of the stomach does not differ significantly.Conclusion. The bacterial composition of the stomach is dependent on the presence of H. pylori. H. pylori leads to the decrease of the bacterial diversity with the predominance of H. pylori in gastric microbiome.